(untitled) (Houndmills, 2006)
Takes into account the specific characteristics embodied in the Doha Development Agenda (DDA). A fifteen-country study, coupled with the global analysis, allows the authors to draw more general conclusions about the poverty impacts of a prospective DDA.
Keywords: International trade,Poverty,Thương mại quốc tế,Đói nghèo; Developing countries,Phát triển quốc gia